Anterior cruciate ligament transection of rabbits alters composition, structure and biomechanics of articular cartilage and chondrocyte deformation 2 weeks post-surgery in a site-specific manner. (2nd January 2020) - Ojanen, Simo P.; Finnilä, Mikko A.J.; Mäkelä, Janne T.A.; Saarela, Kiira; Happonen, Emilia; Herzog, Walter; Saarakkala, Simo; Korhonen, Rami K.
Abstract: Anterior cruciate ligament (ACL) injury often leads to post-traumatic osteoarthritis (OA) and articular cartilage degradation, changing biomechanics of the tissue and chondrocytes, and altering the fixed charged density (FCD) and collagen network. However, changes in these properties are not known at a very early time point after ACL rupture, but recognizing early changes might be crucial for successful intervention. We investigated the effects of ACL transection (ACLT) in rabbits on the site-specific biomechanical properties of articular cartilage and chondrocytes, FCD content and collagen network organization, two weeks post-surgery. Unilateral ACLT was performed in eight rabbits, and femoral condyles, tibial plateaus, femoral grooves and patellae were harvested from experimental and contralateral knee joints. An intact control group was used as a reference. We analyzed chondrocyte morphology under pre- and static loading, cartilage biomechanical properties, FCD content and collagen fibril orientation. ACLT caused FCD loss in the lateral and medial femoral condyle, lateral tibial plateau, femoral groove and patellar cartilage ( p  < 0.05). Minor changes in the collagen orientation occurred in the femoral groove and lateral and medial femoral condyle cartilage ( p  < 0.05). Cartilage stiffness was reduced in the lateral and medial femoral condyles, and chondrocyte biomechanics was altered in the lateral femoral condyle and patellar cartilage ( p  < 0.05). We observed loss of FCD from articular cartilage two weeks after ACLT at several joint locations. These changes may have led to decreased cartilage stiffness and altered cell deformation behavior, especially in the femoral condyles.